"Other Than Mexicans", "Islamic Fascists" and the transatlantic regulation of risky subjects. (April 2015) - Kyriakides, Christopher; Torres, Rodolfo D.
Post-9/11 significations of "immigration threat" link the policing of the US–Mexico border to the "war on terror" geopolitically such that domestic policies and practices related to the regulation of "undocumented" Latino migrants shape and are shaped by extra-domestic considerations related to the signification of Arab and Muslim communities. In broadening migration analysis, to include a geopolitical dimension, we are able to draw out the changing patterns of racialized population regulation within a given territory of the international state complex. Consequently, extending the geopolitical reach to include US and UK post-9/11 security regimes reveals that the logic underpinning the "Other Than Mexican" immigration category in the US, ostensibly an addition to and extension of the signification of threat posed by Latinos to the US, is neither Latino nor US specific: an idiom of threat is mobilized around "special interest aliens" as perpetrators of risk to the global social order, which broadens the domestic reach of state surveillance. The "war on terror" with related discourses of "anti-fundamentalism" and "islamofascism" specifies that risk averse surveillance documents the "elusive undocumented" carrier of terror threat, guilty by association: a cipher of fear is armed and disarmed, used to legitimate and operationalize surveillance as precautionary intervention. Through an analysis of the signification of immigration threat related to the state of Arizona's Support Our Law Enforcement and Safe Neighborhoods Act, SB1070 in 2010 with the judicial investigation surrounding the killing of Brazilian migrant Jean Charles de Menezes by Metropolitan police on the London Underground in 2005, this study reveals how the lethal logic of Other Than Mexican regulation underpins the post-9/11 transatlantic politics of racialized risk, reconfiguring state intervention related to the "browning of America" through an "anti-fundamentalist" population control measure.